2016
DOI: 10.37029/jcas.v2i4.89
|View full text |Cite
|
Sign up to set email alerts
|

An Unusually Prolonged Survival in Metastatic Periampullary Pancreatic Adenocarcinoma

Abstract: Periampullary cancer is the term used for neoplasms arising from the head of pancreas, ampulla of Vater, distal bile duct and periampullary region of duodenum. Of these, the pancreatic adenocarcinoma carries the worst prognosis with majority of mortalities within the 1st year. The overall 5-year survival is <3%. Studies have shown that pancreatic carcinoma has the shortest median survival of 17.1 months of all periampullary carcinomas. With the development of metastasis, the median survival tends to reduce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…In contrast, ampullary carcinomas are primarily in the region of the ampulla of Vater accounting for about 0.2% of tumors of the gastrointestinal tract [1]. Clinically, distinguishing ampullary from periampullary tumors is of high importance as this provides significance to the prognosis and resectability; ampullary carcinomas have a more desirable prognosis with five-year survival ranging from 34%-45% [1,3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, ampullary carcinomas are primarily in the region of the ampulla of Vater accounting for about 0.2% of tumors of the gastrointestinal tract [1]. Clinically, distinguishing ampullary from periampullary tumors is of high importance as this provides significance to the prognosis and resectability; ampullary carcinomas have a more desirable prognosis with five-year survival ranging from 34%-45% [1,3].…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been suggested that patients with periampullary carcinoma of primary duodenal etiology who have had pancreatoduodenectomy have the longest survival at five years (53%) versus other etiologies (22%) [4]. Factors including resection to negative margins, no lymph node metastasis, and well or moderate tumor differentiation have been shown to have a positive impact on five-year survival [3]. Mortality rate after PD is currently 0%-5% in experienced (>25 procedures/year) centers but is still associated with postoperative complications -the most common of these being postoperative infections and sepsis.…”
Section: Discussionmentioning
confidence: 99%